Mineral and fluid inclusions in diamonds from the Urals placers, Russia: Evidence for solid molecular N2 and hydrocarbons in fluid inclusions. (1st December 2019) - Sobolev, Nikolay V.; Logvinova, Alla M.; Tomilenko, Anatoly A.; Wirth, Richard; Bul'bak, Taras A.; Luk'yanova, Lyudmila I.; Fedorova, Ekaterina N.; Reutsky, Vadim N.; Efimova, Emiliya S.
Abstract: The compositions of mineral inclusions from a representative collection (more than 140 samples) of diamonds from the placer deposits in the Ural Mountains were studied to examine their compositional diversity. The overwhelming majority of rounded octahedral and dodecahedral stones typical of placers contain eclogitic (E-type) mineral inclusions (up to 80%) represented by garnets with Mg# 40–75 and Ca# 10–56, including the unique high calcic "grospydite" composition, omphacitic pyroxenes containing up to 65% of jadeite, as well as kyanite, coesite, sulfides, and rutile. Peridotitic (P-type) inclusions are represented by olivine, subcalcic Cr-pyrope, chrome diopside, enstatite and magnesiochromite that are typical for diamonds worldwide. Comparing the chemical composition of olivine, pyrope and magnesiochromite in diamonds of the Urals, north-east of the Siberian platform placers and Arkhangelsk province kimberlites show striking similarity. There are significant differences only in the variations of carbon isotopic composition of the diamonds from the placers of the Urals and north-east of the Siberian platform. One typical rounded dodecahedral diamond was found to contain abundant primary oriented submicrometer-sized (<3.0 µm) octahedral fluid inclusions identified by transmission electron microscopy, which caused the milky color of the entire diamond crystal. The electron energy-loss spectrum of a singular inclusion has a peak at ∼405 eV, indicating that nitrogen is present. The Raman spectra with peaks at 2346–2350 cm −1 confirmed that nitrogen exists in the solid state at room temperature. This means that fossilized pressure inside fluid inclusions may be over 6.0 GPa at room temperature, so the diamond may be considered sublithospheric in origin. However, identification of unique fluid inclusions in one typical placer diamond allows one to expand the pressure limit to at least more than 8.0 GPa. The volatile components of four diamonds from the Urals placers were analyzed by gas chromatography–mass spectrometry (GC–MS). They are represented (rel. %) by hydrocarbons and their derivatives (14.8–78.4), nitrogen and nitrogenated compounds (6.2–81.7), water (2.5–5.5), carbon dioxide (2.8–12.1), and sulfonated compounds (0.01–0.96). It is shown that high-molecular-weight hydrocarbons and their derivatives, including chlorinated, nitrogenated and sulfonated compounds, appear to be stable under upper mantle P-T conditions. A conclusion is drawn that Urals placer diamonds are of kimberlitic origin and are comparable in their high E-type/P-type inclusion ratios to those from the northeastern Siberian platform and in part to diamonds of the Arkhangelsk kimberlite province.